Ribbon-forest und Hecken - Streifenartige Verbreitungsmuster des Baumwuchses an der oberen Waldgrenze in den Rocky Mountains - Holtmeier, Friedrich-Karl (ERDKUNDE, 1982)
Within the forest-tundra-ecotone of the Rocky Mountains ribbon-like structures, which can be attributed to the influence of the wind, can be observed locally. The forest strips run either per pendicular or parallel to the prevailing wind direction (West). Those strips which are oriented approximately normally to the prevailing winds seem to be particular to those ranges of the Rocky Mountains which are rich in snow and dominated by strong and permanent winds from the west. These elongated tree-islands are called ribbons and the intervening wet and treeless meadows snow glades. The ribbons, measuring up to some hundred metres in length and formed of trees (Picea engelmannii, Abies lasiocarpa) up to 15 m in height, act as natural snow fences with big snow masses accumulating at their leeside. Within an area characterized by a more pronounced local relief the distribution of snow must be attributed primarily to the influence of the surface on the windflow just above it, while the effect of the ribbons must be considered as a secondary one. The long-lasting snow cover and the resulting ecological consequences are unfavourable to tree-growth and thus keep the glades (up to 50 m wide) treeless. The ribbon forest occur most frequently on gently sloping surfaces, more or less on the contour, whereas on steep slopes it is less extensive. The forest-strips running parallel to the prevailing winds are called hedges (measuring up to some ten metres in length). In contrast to the ribbons they are common at wind-exposed sites at both the alpine timberline of other high mountains and the polar forest limit. They are caused by the direct physiological and mechanical influences of the winds, which hamper tree-growth on the windward side. Thus the trees are strongly wind-shaped. By layering the trees spread leeward and form the hedges. The narrow wind-channels between the hedges are characterized by a lack of snow during winter rather than a great accumulation as in the case of snow glades. The great abundance of hedges in the Rocky Mountains must be attributed to the permanent influence of westerly winds and to a pronounced ability of the tree species (Picea engelmannii, Abies lasiocarpa, Larix lyallii) to regenerate and spread by layering. In the Rocky Mountains one also finds ribbons formed of close-standing wind-shaped hedges at sites which are characterized by a marked micro-relief. The ribbon-forest, as well as the hedges, should be regarded as typical features of the climax stage of the development of the plant cover at wind-exposed sites near the upper timberline.